The Impact of Human Resource Management Flexibility on Organizational Sustainability / Applied Research in the General Company for Food Products: Pengaruh Fleksibilitas Manajemen Sumber Daya Manusia terhadap Keberlanjutan Organisasi / Penelitian Terapan di Perusahaan Umum Produk Pangan - Assoc. Prof. Dr. Mahmoud Ayed Hassan (Indonesian Journal of Law and Economics Review, 2026)
General Background: Contemporary organizations face dynamic economic and technological changes that require adaptive management approaches. Specific Background: Human resource flexibility, encompassing skill, behavior, and practice dimensions, is considered a critical factor in achieving organizational sustainability through creativity, quality improvement, and operational performance. Knowledge Gap: Despite increasing attention, limited empirical evidence exists regarding how different dimensions of human resource flexibility contribute to sustainability outcomes in industrial organizations. Aims: This study examines the relationship and effect of human resource flexibility on organizational sustainability within the General Company for Food Products. Results: Using a descriptive-analytical approach and regression analysis on 126 respondents, the findings reveal a statistically significant relationship, with human resource flexibility explaining 41% of the variance in organizational sustainability. Among the dimensions, practice flexibility shows the strongest contribution, while efficiency and effectiveness remain relatively weak. Novelty: The study provides empirical evidence linking multidimensional human resource flexibility to sustainability performance in a developing-country industrial context. Implications: The findings highlight the importance of strengthening flexible human resource practices to support sustainable organizational development, particularly by improving efficiency and effectiveness through targeted training and strategic alignment. Keywords: Human Resource Flexibility, Organizational Sustainability, Skill Flexibility, Behavioral Flexibility, Practice Flexibility Key Findings Highlights Practice-related adaptability shows the highest contribution to sustainability performance Moderate sustainability levels indicate uneven development across dimensions Operational performance requires targeted capability development